2017
DOI: 10.1002/da.22591
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of major depression: Their stability, familiality, and prediction by genetic, temperamental, and childhood environmental risk factors

Abstract: The correlations for individual depressive symptoms over multiple episodes and within MZ twins concordant for MD are modest suggesting the important role of transient influences. The multidetermination of individual symptoms was further evidenced by their prediction by personality and exposure to early life adversities. The multiple factors influencing symptomatic presentation in MD may contribute to our difficulties in isolating clinical depressive subtypes with distinct pathophysiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…not a function of the depressive state). Kendler & Aggen (2017) further demonstrated that, within individuals, symptom presentation is only modestly heritable ( r ~0.3) across depressive episodes. These scenarios are not mutually exclusive: indeed, given the complexity of psychopathology, the current results may be due to a combination of ethnicity-specific genetic factors, ascertainment strategy, and the impact of sociocultural/environmental factors on fine-scale clinical heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…not a function of the depressive state). Kendler & Aggen (2017) further demonstrated that, within individuals, symptom presentation is only modestly heritable ( r ~0.3) across depressive episodes. These scenarios are not mutually exclusive: indeed, given the complexity of psychopathology, the current results may be due to a combination of ethnicity-specific genetic factors, ascertainment strategy, and the impact of sociocultural/environmental factors on fine-scale clinical heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, another potential explanation for the overall absence of associations with MDD clinical features is that clinical presentation is pathoplastic (Keller et al 2007; Kendler & Aggen, 2017) – that is, subject to environmental factors and individual variation in risk that is not a function of core physiological processes/genetic liability. Keller et al (2007) reported that MDD symptom endorsement varied in conjunction with exposure to diverse stressful life events, which suggests that genetic factors are not markedly influential on heterogeneity in symptom profiles, assuming environmental risk factors are independent (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The systems exhibit both multifinality (i.e., the same set of causal agents can lead to different mental health outcomes) and equifinality (i.e., diverse causes can produce the same disorder) [4,5]. The systems are heterogeneous, with individuals differing not only in the specific constellation of symptoms experienced, but also in the etiological factors that precede and predict illness onset [6,7]. Further, systems within individuals are dynamic: they rise and fall and evolve over time.…”
Section: Introductionmentioning
confidence: 99%
“…Keller et al (2007) found that chronic stress was associated with some but not all symptoms, such as fatigue and hypersomnia. Likewise, genetic disposition to specific symptoms is uncertain, as Kendler and Aggen (2017) detected only modest concordance of individual MDD symptoms among monozygotic twins, while there were separate environmental factors for different symptoms. Another study found that chronic stress, prior history of depression, higher number of stressful life events, childhood stress, and sex predicted worsening of only certain MDD symptoms (Fried et al, 2014).…”
Section: Differential Validity Of Individual Depressive Symptomsmentioning
confidence: 99%